Effects of exercise on heart rate variability: Inferences from meta-analysis - Sandercock, G. R. H.; Bromley, P. D.; Brodie, D. A. (Medicine & Science in Sports & Exercise, 2005)
Introduction: Chronic exercise training produces a resting bradycardia that is thought to be due partly to enhanced vagal modulation.